A SUSTAINABLE SUPPLY CHAIN MODEL OF RELATIONSHIP BETWEEN WOOD SUPPLIER AND FURNITURE INDUSTRY IN INDONESIA - Muh. Hisjam Adi Djoko Guritno; Shalihuddin Djalal Tandjung (Universitas Gadjah Mada, 2012)
Wooden furniture industry is an important industry sector in Indonesia, because many people’s welfare relyon this industry sector and the industry has a big social and environmental impacts. Many wooden furnitureindustries in Indonesia, especially in Central Java Province face problems related to the sustainability. The relationbetween wood suppliers and furniture industry is studied in this paper. A sustainable supply chain management (s-SCM) model is proposed as an approach for solutions for the problems. The approach is chosen due to the characteristics of the problems that related to economic, social, and environmental problems. This aim of this paper is to determine how much supply teak wood must be provided by PP to satisfy furniture industry demand, how much production capacity that must be increased and how large forest area that must be planted in order to achieve environmental and social goals without sacrificing economical goals much. Goal programming (GP) is chosen for solving the problems, because the goals are to maximize the total benefit,minimize the total loss and anticipate the conflicts between goals. Numerical trial based on observation in teak wooden furniture industry in Central Java was used to illustrate our findings. Using pareto efficient principle, the model can satisfy all goals that need to be achieved. Numerical results can be used by decision makers in teak wood industry to analyze the trade-off among several set of alternative solutions.